2012
DOI: 10.2174/157015912804499537
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Inhibitors in Tuberous Sclerosis Complex

Abstract: Tuberous sclerosis complex (TSC) is a genetic multiple organ system disorder that is characterized by the development of tumor-like lesions (hamartomas) and neurodevelopmental disorders. Mutations in the TSC1 and TSC2 tumor suppressor genes occur in the majority of patients with TSC, resulting in hyperactivation of the mammalian target of rapamycin (mTOR) signaling pathway and subsequent abnormalities in numerous cell processes. As a result, mTOR inhibitors such as sirolimus and everolimus have the potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(25 citation statements)
references
References 49 publications
0
21
0
4
Order By: Relevance
“…In addition, a number of novel medical therapies for renal AMLs in TSC have been identified (12,(22)(23)(24). After the identification of TSC1 and TSC2 and their encoded proteins (hamartin and tuberin, respectively), the mammalian target of rapamycin (mTOR) complex1 was established as a downstream target of the hamartin/tuberin complex.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a number of novel medical therapies for renal AMLs in TSC have been identified (12,(22)(23)(24). After the identification of TSC1 and TSC2 and their encoded proteins (hamartin and tuberin, respectively), the mammalian target of rapamycin (mTOR) complex1 was established as a downstream target of the hamartin/tuberin complex.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…After the identification of TSC1 and TSC2 and their encoded proteins (hamartin and tuberin, respectively), the mammalian target of rapamycin (mTOR) complex1 was established as a downstream target of the hamartin/tuberin complex. Therefore, the use of mTOR inhibitors (mTORis) may present a potential targeted therapy as they have been demonstrated to affect the AML volume (12,(22)(23)(24). A multicentre randomized double-blind placebo-controlled trial by Bissler et al (25) demonstrated that everolimus, an mTORi, was more effective than a placebo in AML response rate (42 vs. 0%), skin lesion response rate (26 vs. 0%), and the median time to AML progression was 11.4 months for the placebo and was not reached for everolimus.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
“…Ингибиторы mTOR также приводили к улучшению обучения [6]. Все вы-шесказанное приводило к уменьшению фенотипиче-ских проявлений туберозного склероза и увеличению выживаемости экспериментальных животных [7].…”
unclassified
“…Эверо-лимус является его производным, созданным с целью улучшения фармакокинетики. Он структурно напоми-нает сиролимус, но обладает большей стабильностью, растворимостью и другими более благоприятными фармакокинетическими характеристиками [7]. Меха-низм действия эверолимуса, как и других производных рапамицина, заключается в связывании с внутрикле-точным белком FK506, что в свою очередь блокирует киназу mTOR.…”
unclassified
See 1 more Smart Citation